Marketing Analysis of Processed Fishery Products using Interactive Media - Ndatangara, Verderika; Fachry, Mardiana Erthrawaty; Adhawati, Sri Suro (International Journal of Environment, Agriculture and Biotechnology, 2019)
This study aims to analyze marketing of processed fishery products by using interactive media in Makassar conducted in April - June 2019 took place in the city of Makassar. Data was collected through interviews, observations, questionnaires and literature study. The research method in this study is a descriptive analysis will present a general overview of SMEs marketing of processed fish products as a whole by focusing on marketing by using interactive media. Samples are processed fishery products 8 SMEs located in the city of Makassar with criteria using the owners use at least 2 social media and has been operating for less than 5 years. The results showed that social media are the most widely used in the sales activity (75%) is WhatsApp, Facebook and Instagram. Group 2 media (12.5%) only uses WhatsApp and Facebook and group 4 media (12.5%) using WhatsApp, Facebook, Instagram and Line.. The percentage of consumers prefer buying fishery products in a row is a promotion, place, price and product.